1972
DOI: 10.1136/jcp.25.8.657
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibrin deposition in diabetic glomerulosclerosis: a light, electron and immunofluorescence microscopy study

Abstract: There is much evidence to suggest that the microvasculature in diabetic subjects is hyperpermeable to certain plasma constituents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Indeed, fibrin and mesan- giolysis were observed less commonly in some recent pathologic studies of diabetic nephropathy (3). However, in the older literature, numerous studies demonstrated the activation of intrarenal coagulation as well as fibrin deposition (41,42) in association with mesangiolysis and mesangial nodule formation (42). We believe that this was observed more commonly in the past, before the use of effective antihypertensive agents and better blood sugar control.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, fibrin and mesan- giolysis were observed less commonly in some recent pathologic studies of diabetic nephropathy (3). However, in the older literature, numerous studies demonstrated the activation of intrarenal coagulation as well as fibrin deposition (41,42) in association with mesangiolysis and mesangial nodule formation (42). We believe that this was observed more commonly in the past, before the use of effective antihypertensive agents and better blood sugar control.…”
Section: Discussionmentioning
confidence: 84%
“…4) They concluded that endothelial and mesangial trapping of fibrinogen and/or other macromolecules might initiate or accelerate mesangial enlargement and irregularities of the basement membrane. In glomerulonephritis, intraglomerular coagulation with fibrin deposition was also suggested to be involved in the development of glomerular injury.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Also in human and experimental diabetic nephropathy, glomerular fibrin deposition and extracellular matrix (ECM) expansion have been noted. 4,5) In this context, transforming growth factor b (TGF-b) is upregulated in kidney diseases, and TGF-b promotes the production of various ECM proteins. 6) Regarding its relationship with coagulation, thrombin stimulates TGF-b production in mesangial cells in vitro.…”
mentioning
confidence: 99%
“…Fibrin/fibrinogen deposition in the glomeruli is a common feature of diabetic nephropathy [4, 5], suggesting that coagulation activation may be involved in the pathogenesis of diabetic renal disease. Furthermore, several reports claim that diabetes mellitus is associated with changes in the hemostatic system [6,7,8].…”
Section: Introductionmentioning
confidence: 99%